KEPEMIMPINAN PEREMPUAN DALAM PERSPEKTIF PENDIDIKAN ISLAM MENURUT HJ. NURLELA MUBAROK - Mukh. Adib Shofawi; Novan Ardy Wiyani (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2021)
This study aims to describe the concept of women's leadership in the perspective of Islamic education according to Hj. Nurlela Mubarok. The type of research used is character study research, namely Hj. Nurlela Mubarok. Data was collected by interview, observation and documentation, then analyzed in three stages, namely data reduction, data display and verification. The results of the study show that: First, women's leadership is identical with the ability to influence others through the use of a distinctive image that exists in women in order to realize organizational goals. Second, the characteristics of women leaders emphasize more on the personal image of women when they become leaders, so that it affects their leadership in the organization. Third, the advantages of female leaders are still closely related to the characteristics of women themselves. Fourth, the shortage of women leaders has an impact on the individuals and organizations they lead. These impacts include hampered institutional development, as well as personal leaders who are less than optimal in carrying out their leadership roles. These four things illustrate that women in an educational institution are actually able to compete in their work so that they also have the ability to become a leader.